2014
DOI: 10.1038/ncomms5758
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical and asymmetrical division analysis provides evidence for a hierarchy of prostate epithelial cell lineages

Abstract: Although symmetrical and asymmetrical divisions of stem cells have been extensively studied in invertebrate and mammalian neural epithelia, their role remains largely unknown in mammalian non-neural epithelial development, regeneration and tumorigenesis. Here, using basal and luminal cell-specific markers and cell lineage tracing transgenic mice, we report that in developing prostatic epithelia, basal and luminal cells exhibit distinct division modes. While basal cells display both symmetric and asymmetric div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 51 publications
7
85
0
Order By: Relevance
“…In this study, we initiated the tracing in the prostate at a different time point than in the MG to assess the fate of BCs during prostate postnatal development (which has been previously described) Table S6 for further information on statistics. (Ousset et al 2012;Pignon et al 2013;Wang et al 2014). If we had performed the tracing in the prostate at the same time point as in the MG, when the postnatal development of the prostate is largely completed, we would have assessed the fate of the unipotent SCs that sustain prostate adult homeostasis (Wang et al , 2013(Wang et al , 2014Liu et al 2011;Choi et al 2012;Ousset et al 2012;Lu et al 2013;Pignon et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we initiated the tracing in the prostate at a different time point than in the MG to assess the fate of BCs during prostate postnatal development (which has been previously described) Table S6 for further information on statistics. (Ousset et al 2012;Pignon et al 2013;Wang et al 2014). If we had performed the tracing in the prostate at the same time point as in the MG, when the postnatal development of the prostate is largely completed, we would have assessed the fate of the unipotent SCs that sustain prostate adult homeostasis (Wang et al , 2013(Wang et al , 2014Liu et al 2011;Choi et al 2012;Ousset et al 2012;Lu et al 2013;Pignon et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Lineage tracing experiments during prostate postnatal development, adult homeostasis, and adult regeneration after castration suggested that prostate postnatal development is mediated by multipotent and unipotent SCs, whereas adult prostate maintenance and regeneration are mediated by basal and luminal unipotent SCs (Wang et al , 2013(Wang et al , 2014Liu et al 2011;Choi et al 2012;Ousset et al 2012;Lu et al 2013;Pignon et al 2013).…”
Section: Biostatistical Analysis Of Multicolor Clonal Tracing Demonstmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, both luminal and basal compartments contain singlelineage P-SCs that only give rise to daughter cells in their respective compartments (7,8). Interestingly, the basal cells display both symmetrical and asymmetrical divisions, whereas luminal cells only exhibit symmetrical divisions (9). Asymmetrical divisions of stem cells reflect their capacity to self-renew and produce daughter cells for differentiated progeny.…”
mentioning
confidence: 99%
“…(continued) Wang et al 2014). Later, Rios et al highlighting the potential caveats of these approaches identified a single bipotent stem cell in the mammary gland (Rios et al 2014).…”
Section: Overview Of the Evolution Of The Cancer Stem Cell Modelmentioning
confidence: 93%